Acoustic Measurements and Correction of a Council Room. (September 2014) - Iannace, Gino; Trematerra, Amelia
This paper presents the acoustic correction of a Council Room, with an original reverberation time of 1.0 kHz higher than 3.0 seconds and marble floors walls and ceiling in plaster smooth. The work was conducted in four phases: the first was the measurement of acoustic characteristics with the empty hall; the second phase was the identification of the soundproof material for the acoustic correction and the measurement of the absorption coefficients with the tube of "Kundt"; the third phase was the implementation of a numerical model with the software "Odeon" to choose the position of absorbent material and of the plaster surface to be coated; the latest phase, after the installation of soundproof panels, was the acoustic measurement to verify if the results of the acoustic measurements are equal to those one of the numerical model.